Temporal relationship between dysthymia and temporomandibular disorder: a population-based matched case-control study in Taiwan. Issue 1 (December 2017) - Lin, Shang-Lun; Wu, Shang-Liang; Ko, Shun-Yao; Yen, Ching-Yu; Chiang, Wei-Fan; Yang, Jung-Wu
Abstract Background Numerous studies have reported a relationship between depression and temporomandibular disorders (TMD), but the conclusions remain undefined. The aim of this article was to examine the temporal relationship between depression and TMD. Methods In this retrospective matched case-control study, we recruited all samples from a randomsample sub-dataset of one million insured individuals for the year 2005 (Longitudinal Health Insurance Database (LHID2005)). All beneficiaries were enrolled in the National Health Insurance (NHI) programme in Taiwan. We used propensity scoring and matched the case and control groups (1:1) by ten confounding factors to detect the effect of different types of depression on TMD. Results The positive correlative factors of TMD included the total number of times medical advice was sought for an unspecified anomaly of jaw size plus malocclusion (TTSMA-JS, p  = 0.045), the total number of times medical advice was sought for an anxiety state (TTSMA-AS, p  = 0.000), and the total number of times medical advice was sought for a panic disorder (TTSMA-P, p  = 0.009). Dysthymia (synonymous with chronic depression) had an effect on TMD. The odds ratio (OR) of dysthymia for TMD measured by multiple logistic regression was 1.91 (p  = 0.008) after adjusting for demographic factors, psychiatric comorbidities, and maxillofacial confounders. Conclusions This study demonstrated the established temporal relationship between dysthymia and TMD. The inclusion of a psychiatrist on the TMD management team is appropriate.